Student employment: Advantage or handicap for academic achievement? - Maresa Sprietsma (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
We estimate the effects of student employment on academic performance. Performance is measured by grades achieved one and a half years after entering university. We use the amount of financial aid students receive after application as a source of exogenous variation in the probability or being employed to correct for potential endogeneity bias. We find no evidence that student employment is detrimental to academic performance, even for a larger number of hours worked per week. There is significant selection of students into different types of student employment.
urn:nbn:de:bsz:180-madoc-404713
Keywords: J31; J61; 330; student employment; academic achievement; tertiary education